The Role of Social Support as a Predictor of Teacher's Subjective Well-being - Asfari, Nur Amin Barokah; Utomo, Hanggara Budi; Margandhi, Callista Justine (KnE Social Sciences, 2024)
This study aims to examine the role of social support as a predictor of subjective wellbeing in teachers. Participants in this study were 138 teachers (37 male and 101 female; 31 civil servants and 107 private/honorary teachers). SWB was measured with the Scale of Positive and Negative Experiences (SPANE) which measures the cognitive dimension including positive affect and negative affect and the Satisfaction with Life Scale (SWLS) which measures the affective dimension of SWB. Social support was measured with R-MSPSS which measures the perception of social support received, which comes from the principal, colleagues, family, and friends. The results of descriptive analysis showed that most of the participants’ SWB was at a moderate level, both measured overall and in terms of each dimension (nswb=95 (68.1%); npositive=98 (68.8%); nnegative=93 (67.4%); nsatisfaction=93 (67.4%)). Hypothesis testing was done with regression analysis and it was found that social support acts as a predictor of teacher SWB (R=0.199; R2=0.0395; F=5.59; p=0.019). The results of the analysis per dimension of social support show that only support from family has a significant role as a predictor of SWB (p=0.002). This is possible because most of the participants are female so when teachers feel they get social support from their families, it can reduce stress levels, both from work and dual role conflict, thus affecting SWB. Keywords: social support, subjective well-being, teacher